MARKETING THROUGH OMNICHANNEL SHOPPING EXPERIENCE TO IMPROVE CUSTOMER CITIZENSHIP BEHAVIOR - Ghazian, Geri; Masinta, Yolanda; Kurniawati, Kurniawati (Distribusi - Journal of Management and Business, 2025)
The growing popularity of mobile devices and the expansion of internet usage have triggered an increase in online purchases. In addition to that, offline purchases and coming directly to the store are also some of the choices of some customers. As the business competition of retail stores in Indonesia increases, customers choose several options for purchasing goods through omnichannel. This research was written to find out more about the effect of marketing through omnichannel shopping experience to increase customer citizenship behavior through customer engagement and customer satisfaction in retail companies in Jabodetabek. This article uses the SEM method and data processing with AMOS. The sampling method uses non-probability sampling with omnichannel shopping customers from the age of 17 years and above. The study results reveal that the personalization factor in omnichannel supports customer engagement and customer satisfaction, both of which are customer citizenship behaviors. This study contributes to the marketing literature by investigating dimensions of omnichannel shopping experience and their impact on customer engagement and customer satisfaction and its also impact on customer citizenship behavior. Furthermore, the study contributes to omnichannel retail stores in Indonesia, especially in the Jabodetabek area.